2010
DOI: 10.1021/nl1034495
|View full text |Cite
|
Sign up to set email alerts
|

Vertically Aligned Cadmium Chalcogenide Nanowire Arrays on Muscovite Mica: A Demonstration of Epitaxial Growth Strategy

Abstract: We report a strategy for achieving epitaxial, vertically aligned cadmium chalcogenide (CdS, CdSe, and CdTe) nanowire arrays utilizing van der Waals epitaxy with (001) muscovite mica substrate. The nanowires, grown from a vapor transport process, exhibited diameter uniformity throughout their length, sharp interface to the substrate, and positive correlation between diameter and length with preferential growth direction of [0001] for the monocrystalline wurtzite CdS and CdSe nanowires, but of [111] for zinc ble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 49 publications
5
87
0
Order By: Relevance
“…Noncovalent epitaxy, the so-called van der Waals (vdW) epitaxy, [15][16][17][18] has the ability to produce single-crystalline semiconductor nanostructures with an abrupt clean heterointerface and suppressed threading dislocation density, even for highly latticemismatched heteroepitaxial systems. 19 Accordingly, it is well suited for fabricating high-quality epitaxial semiconductor/hBN heterostructures for diverse device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Noncovalent epitaxy, the so-called van der Waals (vdW) epitaxy, [15][16][17][18] has the ability to produce single-crystalline semiconductor nanostructures with an abrupt clean heterointerface and suppressed threading dislocation density, even for highly latticemismatched heteroepitaxial systems. 19 Accordingly, it is well suited for fabricating high-quality epitaxial semiconductor/hBN heterostructures for diverse device applications.…”
Section: Introductionmentioning
confidence: 99%
“…Many II-IV group nanorods, such as CdS, CdSe, CdTe, ZnS, ZnSe, and ZnTe, have been successfully synthesized in colloidal solutions [17][18][19][20][21][22]. However, except ZnO [23], there are only a few reports that describe the fabrication of aligned II-IV nanorod or nanowire arrays without involving of catalyst and/or templates [24][25][26][27][28]. Xiong et al have succeeded in growing the CdS, CdSe, and CdTe nanorod arrays on meca using CVD method [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…However, except ZnO [23], there are only a few reports that describe the fabrication of aligned II-IV nanorod or nanowire arrays without involving of catalyst and/or templates [24][25][26][27][28]. Xiong et al have succeeded in growing the CdS, CdSe, and CdTe nanorod arrays on meca using CVD method [24,25]. Qian et al and Jiang et al have independently reported the synthesis of ordered arrays of wurtzite CdS nanowires on Cd-foil substrates via solvothermal route [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Although both the mica and the Bi 2 Te 3 thin film have a nature of layered structure, the oscillations featured in the lower energy portion of the spectra can be mainly associated with the interference of the wave reflected in between the layers of mica, given the fact that the mica substrate is four orders of magnitude thicker than the Bi 2 Te 3 thin films. 26 To summarize, high-quality Bi 2 Te 3 thin films exhibiting atomically smooth terraces over several microns have been fabricated on insulating and flexible mica substrates by MBE. The relatively large phase coherence length of relatively thin samples extracted from the WAL effect, and the high mobility deduced by the quantum oscillations can be attributed to the reduced defect density epilayer grown by means of vdWE.…”
mentioning
confidence: 99%